2020
DOI: 10.1039/c9fo01009b
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber isolated from sweet potato residues promotes a healthy gut microbiome profile

Abstract: This study investigated the impact of dietary fiber from sweet potato residue (SPDF) on the diversity of the gut microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…In recent years, dietary fibre has received increasing attention from researchers and industry due to its potential beneficial effects on the reduction of coronary heart disease, type 2 diabetes, obesity and constipation (Delzenne et al ., 2020; Liu et al ., 2020; Zamaratskaia et al ., 2020). Whole grain components used to obtain dietary fibre, such as wheat bran, have caught the attention of researchers and proven to be a potential source of dietary fibre.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, dietary fibre has received increasing attention from researchers and industry due to its potential beneficial effects on the reduction of coronary heart disease, type 2 diabetes, obesity and constipation (Delzenne et al ., 2020; Liu et al ., 2020; Zamaratskaia et al ., 2020). Whole grain components used to obtain dietary fibre, such as wheat bran, have caught the attention of researchers and proven to be a potential source of dietary fibre.…”
Section: Introductionmentioning
confidence: 99%
“…Overall this suggests that even for common, well-studied microorganisms a surprising amount of intra-species genomic diversity and associated biochemical functions still remains to be categorized. These findings continue to support the GI-tract microbiome as being an extremely active, dynamic and changing ecosystem dependent on the host's age, diet, habits, environment, ethnicity, and health and/or disease status [86][87][88][89], and that lifestyle choices and environmental variables including for example, the host's choice of geographical and environmental location has a significant bearing on both the dynamic composition of their microbiome and through this their overall health status [90][91][92][93][94][95][96][97][98][99][100].…”
Section: Environment and Lifestylementioning
confidence: 99%
“…This approach might be especially useful in those disorders resistant to pharmacological-or immunological-based therapies. For example, experiments in transgenic murine models as well as emerging human clinical studies have revealed that therapeutic manipulation of the microbiota, using fecal microbial transplantation, natural or engineered probiotics, or pre-biotics represent effective nontoxic and non-invasive approaches for the treatment, clinical management and/or prevention of for example, allergies, autoimmune diseases, Clostridium difficile infection and enhance the efficacy of certain cancer immune-therapeutics, especially in the elderly [21,30,89,[95][96][97][98][99][100]. Preliminary results from our own laboratory using the 5xFAD amyloid-overexpressing murine mouse model of AD (containing 5 familial Alzheimer's disease genes and based on a C57BL6 murine background) shows that animals fed high-fiber (both soluble and insoluble) diets have a lower abundance of B. fragilis in their GI-tract microbiome compared to age-matched control mice receiving standard diets, and show significant improvement in cognition and memory tasks as they age (manuscript in preparation).…”
Section: Use Of Probiotic And/or Prebiotic To Approaches To Optimize Human Healthmentioning
confidence: 99%
“…2A), a high dose of sweet potato polysaccharide might decrease the abundance of gut microbiota. 34 So 400 mg kg À1 of WPSPP-1 was used in in vivo experiments.…”
Section: 3mentioning
confidence: 99%